Non-Orthogonal Multiple Access With Alamouti Space-Time Block Coding - Toka, Mesut; Kucur, Oğuz (IEEE-Inst Electrical Electronics Engineers Inc, 2018)
In this letter, we investigate the combination of non-orthogonal multiple access (NOMA) with the conventional Alamouti space-time block coding scheme over Nakagami-m fading environments. In the network, one base station serves multiple users simultaneously by using Alamouti scheme. The exact outage probability (OP) expression is obtained in closed-form. Moreover, asymptotic analysis is also conducted to provide more insights into the OP through diversity order and array gain. The theoretical results verified by the Monte Carlo simulations show that Alamouti scheme can double the diversity order of NOMA network, which also depends on Nakagami channel parameter m and user's ordinal number.
Keywords: Non-orthogonal multiple access; Alamouti code; outage probability; diversity order